Rigid Bronchoscopy in Airway Foreign Bodies: Value of the Clinical and Radiological Signs - Acharya,Kunjan (2016)
Abstract Introduction Foreign body in airway is a common emergency in ENT practice. As we know, Rigid Bronchoscopy is the method of choice for removing it, although at times it leads to specialists performing unnecessary bronchoscopy, exposing patients to hazards of general anesthesia. Objective The objective of my study is to calculate sensitivity, specificity, positive predictive value, odds ratio from the clinical and radiological signs, comparing with the gold standard, the rigid bronchoscope procedure. Method This is a prospective analytical study designed at University Teaching Hospital and conducted over a period of 18 months, from March 2011 to August 2012. Data collection was broadly classified into three different categories: (1) Symptomatology, such as presence or absence of choking, cyanosis, and difficulty in breathing; (2) Clinical signs, such as the presence or absence of air entry, crackles, and rhonchi 3. Chest X-ray findings were suggestive of a foreign body. Results There were a total of 40 rigid bronchoscopies performed under general anesthesia for the diagnosis and therapeutic reasons. Among 40 patients who underwent rigid bronchoscopy, 32 (80%) were found to have varieties of foreign bodies in their airway while 8 patients (20%) had negative bronchoscopy. The history of choking is the only clinical symptoms which came out to be statistically Significant (p = 0.043) with odds ratio of 5. Conclusion Rigid bronchoscopy is the gold standard technique for diagnosis and procedure of choice to remove FB from airway. Regardless, it still presents a small chance of negative result, especially when there is no history of aspiration. received